PENENTU KEBIJAKAN DIVIDEN DAN KONSEKUENSINYA TERHADAP NILAI PERUSAHAAN (Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2009-2013) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to look at the effect of liquidity, leverage, profitability, firm size and sales growth on dividend policy and dividend policy influence on the value of the company on manufacturing companies listed in Indonesia Stock Exchange 2009-2013 period. The populations in this study are manufacturing companies listed in Indonesia Stock Exchange 2009-2013. Sample in this study using purposive sampling method, amounting to 32 companies. The Results obtained in this study are variable liquidity, leverage and profitability significantly negative effect on dividend policy. Company size and sales growth have no effect on dividend policy. While the variable dividend policy does not effect the value of the company.Keywords: Dividend Policy, Coorporate Value